1970
DOI: 10.3329/bjch.v34i1.5694
|View full text |Cite
|
Sign up to set email alerts
|

Liver Biopsy in Children in Dhaka Shishu Hospital A Study of 30 Cases

Abstract: Background: Liver biopsy is an established procedure to diagnose disease, to assessprognosis and to follow up of liver diseases. Although liver biopsy is a confirmatory diagnosticprocedure of majority of the hepatological disorders, it carries the risk of complications.Though major complications rarely occur, minor complications are common. To minimizecomplications, several biopsy techniques have been developed. The present study wasintended to correlate the clinical diagnoses with histological diagnoses and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…6 Pain after LB is mild, well tolerated and controlled by minor analgesia. 9 In the present study, only mild pain & discomfort were found in 38.3% cases where diffuse pain that required analgesics were found only 18.3% cases which is quite similar as shown by Alam et al 11 (36.7% and 10% respectively). There are two factors demonstrated to be associated with an intense pain requiring analgesics: cutting biopsy needles and less experienced operators.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…6 Pain after LB is mild, well tolerated and controlled by minor analgesia. 9 In the present study, only mild pain & discomfort were found in 38.3% cases where diffuse pain that required analgesics were found only 18.3% cases which is quite similar as shown by Alam et al 11 (36.7% and 10% respectively). There are two factors demonstrated to be associated with an intense pain requiring analgesics: cutting biopsy needles and less experienced operators.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, majority of children were less than 1 year of age (43.3%) and in the other studies (For example, Alam et al 11 ), most of the children were 1-5 years (46.7%) and >5 years (50.0%) age group. In our study, chronic hepatitis (10.0%), glycogen storage disease (10.0%), cirrhosis (6.7%) and hepatoblastoma (6.7%) were found in moderate frequency.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations